(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of the article is to analyze and assess the sectoral diversity of changes of labor productivity in Poland. The study highlighted the issues of the relationship between changes in labor productivity, employment changes and changes in the average monthly wage by sector. The research problem was formulated in the form of a research question, whether the sectoral diversification of changes in labor productivity is observed in the Polish economy and if so, whether changes in employment and wages in sectors follow the changes in labor productivity? The analysis uses BDL GUS data for the Polish sectors-aggregated economy for the period 2005-2015. The general conclusion from the analysis of empirical data, can be formulated as follows: changes in labor productivity in Poland are diversified, with significant increases in labor productivity accompanied by small increases in employment and higher increases in monthly wages.